Faktor yang Mempengaruhi Tax Avoidance dengan Ukuran Perusahaan sebagai Variabel Kontrol - Mariani, Desy; Suryani, Suryani (Institut Bisnis dan Informatika Kesatuan, 2021)
For companies, taxes are costs that reduce profits. The company wants to pay the minimum tax so that the profit earned by the company does not decrease, while from the government side, tax collection is used to finance the implementation of state development. This difference also causes taxpayers to tend to avoid taxes to reduce their tax burden, so that state revenue from the tax sector is still not maximized. This study aims to determine the factors that affect tax avoidance with company size as a control variable. This study uses a sample of trading, service and investment companies in the wholesale and retail trade sub-sector listed on the Indonesia Stock Exchange for the period 2014-2018. The sampling method used in this study was purposive sampling method, where according to the established criteria, 22 companies were obtained and the data used were secondary data. The analysis technique used in this study is multiple linear regression analysis using the Statistical Product and Service Solutions (SPSS) v.20.0 program. The results show that Leverage, Sales Growth and Company Size have a positive effect on tax avoidance, while liquidity and fixed asset intensity have no effect on tax avoidance, thus company size can control Leverage and Sales Growth to influence tax avoidance.